S100A12 Expression Is Modulated During Monocyte Differentiation and Reflects Periodontitis Severity - Lira-Junior, Ronaldo; Holmström, Sofia Björnfot; Clark, Reuben; Zwicker, Stephanie; Majster, Mirjam; Johannsen, Gunnar; Axtelius, Björn; Åkerman, Sigvard; Svensson, Mattias; Klinge, Björn; Boström, Elisabeth A. (Frontiers in Immunology, 2020)
S100A12 is a calcium-binding protein of the S100 subfamily of myeloid-related proteins that acts as an alarmin to induce a pro-inflammatory innate immune response. It has been linked to several chronic inflammatory diseases, however its role in the common oral immunopathology periodontitis is largely unknown. Previous in vitro monoculture experiments indicate that S100A12 production decreases during monocyte differentiation stages, while the regulation within tissue is poorly defined. This study evaluated S100A12 expression in monocyte subsets, during monocyte-to-macrophage differentiation and following polarization, both in monoculture and in a tissue context, utilizing a three-dimensional co-culture oral tissue model. Further, we explored the involvement of S100A12 in periodontitis by analyzing its expression in peripheral circulation and gingival tissue, as well as in saliva. We found that S100A12 expression was higher in classical than in non-classical monocytes. S100A12 expression and protein secretion declined significantly during monocyte-to-macrophage differentiation, while polarization of monocyte-derived macrophages had no effect on either. Peripheral monocytes from periodontitis patients had higher S100A12 expression than monocytes from controls, a difference particularly observed in the intermediate and non-classical monocyte subsets. Further, monocytes from periodontitis patients displayed an increased secretion of S100A12 compared with monocytes from controls. In oral tissue cultures, monocyte differentiation resulted in increased S100A12 secretion over time, which further increased after inflammatory stimuli. Likewise, S100A12 expression was higher in gingival tissue from periodontitis patients where monocyte-derived cells exhibited higher expression of S100A12 in comparison to non-periodontitis tissue. In line with our findings, patients with severe periodontitis had significantly higher levels of S100A12 in saliva compared to non-periodontitis patients, and the levels correlated to clinical periodontal parameters. Taken together, S100A12 is predominantly secreted by monocytes rather than by monocyte-derived cells. Moreover, S100A12 is increased in inflamed tissue cultures, potentially as a result of enhanced production by monocyte-derived cells. This study implicates the involvement of S100A12 in periodontitis pathogenesis, as evidenced by increased S100A12 expression in inflamed gingival tissue, which may be due to altered circulatory monocytes in periodontitis.